TESTICULAR VERSUS EPIDIDYMAL SPERMATOZOA IN INTRACYTOPLASMIC SPERM INJECTION TREATMENT CYCLES - Hameed, Hameed N; Ozturk, Ozturk O (Journal of Ayub Medical College Abbottabad, 2010)
Background: Normal fertilization and ongoing pregnancy can be achieved using intracytoplasmic sperm injection (ICSI), even with severely immature spermatozoa. However, the published literature documents conflicting results as to the outcome of ICSI. Methods: Surgical extraction of spermatozoa in 111 ICSI treatment cycles performed over five years at the Assisted Conception Unit (ACU), University College Hospital (UCH), was retrospectively evaluated to compare the outcome of ICSI treatment using either testicular or epididymal spermatozoa. Results: A higher normal fertilization rate and lower abnormal fertilization rate was observed in the epididymal spermatozoa group than in the testicular spermatozoa group. Embryo development on day 3 after fertilization and implantation was significantly better in the epididymal spermatozoa group. Clinical and ongoing pregnancy rates were higher and the spontaneous miscarriage rate lower in the epididymal spermatozoa group, but only the clinical pregnancy rate reached statistical significance. Conclusions: The origin of surgically extracted spermatozoa has an effect on the success of assisted reproduction using ICSI, and the immaturity of testicular spermatozoa may affect fertilization, embryo development, implantation and pregnancy. Keywords: IVF, male factor, azoospermia, surgical extraction of spermatozoa, outcome